A Traditional Literature Review on Physicians’ Dual Practice: Literature Review - Kirathimo MURUGA; Tatjana VASILJEVA (Communications of International Proceedings, 2022)
Research motivation: The current study seeks to establish the trends in physician’s dual practice and present existing knowledge gaps that need to be filled based on studies done in other contexts.   Research Design/methodology: The study adopted a desktop literature review method. This involved an in-depth review of studies related to physicians’ dual practice where the researcher arrived at 32 articles that were suitable for analysis.  Main findings: The study proves the necessity of the studies to be carried out in the low and middle earning countries of which most are situated in the Sub-Saharan and Asian region. A trend analysis supported the above mentioned by indicating that over the period the studies were researched. Dual practice has been receiving the concerns by various authors. This was drawn from the upwards increasing trend in the subject of the study (Multiple Job holding, dual practice, moonlighting as well as physicians’ dual practice) since 2012 to 2019. The survey likewise found that descriptive research design was the trending technique to survey studies on dual practice.  Implications: Based on the survey findings, the study recommends that dual practice is a maiden study in Kenya that other authors from Sub-Saharan Africa can use to base future studies on. Findings from this study may be used to shape policy in the area of managing contracts for physicians in dual practice.
Keywords: Physician’s dual practice; dual job holding; moonlighting; multiple job holding.